1982
DOI: 10.1017/s0010417500010203
|View full text |Cite
|
Sign up to set email alerts
|

Corsets and Conception: Fashion and Demographic Trends in the Nineteenth Century

Abstract: It is generally accepted that declining birth rates in most Western countries after the late 1870s2 were preceded by declining marital fertility among the middle classes. Though some scholars have suggested that the general decline was due partly to the working classes' later emulation of the middleclass family size “ideal,” no hypothesis has been presented to explain satisfactorily the downward trend in middle-class fertility. The most widely accepted explanation is that the “great depression” of 1873–96 lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
6
0
7
Order By: Relevance
“…Singh argues that this preference enhances reproductive success because low WHRs, which are associated with female sex hormones, are a reliable signal of reproductive potential and health. Corsets, girdles and belts have long been used to exploit this male preference (Davies, 1982). The contribution of low WHR to attractiveness may not, however, be as great as initially thought, because its eåect is much reduced when the eåect of body mass index (weight scaled to height) is removed Tove !…”
mentioning
confidence: 99%
“…Singh argues that this preference enhances reproductive success because low WHRs, which are associated with female sex hormones, are a reliable signal of reproductive potential and health. Corsets, girdles and belts have long been used to exploit this male preference (Davies, 1982). The contribution of low WHR to attractiveness may not, however, be as great as initially thought, because its eåect is much reduced when the eåect of body mass index (weight scaled to height) is removed Tove !…”
mentioning
confidence: 99%
“…Richardson and Kroeber (1973) found that women's waistlines were at the smallest between 1841 and 1870. Women that practiced tight-lacing endured many physical restrictions including constipation, indigestion, headaches, backaches, respiratory problems, fainting, anemia, nausea, vomiting, and abscesses (Davies 1982). It is possible that the woman from Lexington did not frequently wear tight-laced clothing because of difficulties with tuberculosis and her lifestyle on the frontier.…”
Section: Lifestylementioning
confidence: 99%
“…The once popular custom of wearing corsets altered the shape of a woman's pelvis and displaced her internal organs. This led to shortness of breath, frequent fainting, painful intercourse and frigidity, birthing problems, and elevated neonatal and maternal mortality (Davies, 1982).…”
Section: Statusmentioning
confidence: 99%
“…Perhaps having a thinner waist due to infrequent use of a corset did give certain nineteenth century women a n advantage over nonusers in terms of local notions of mate desirability. Yet, when most women of high rank resorted to this avenue of enhancing their attractiveness, some females went to the extreme, with significant somatic and reproductive complications (Davies, 1982). Competition also may pertain to traits such as foot-binding, which Crook (1981) has explained as male insurance against cuckoldry: a wife who cannot walk is unlikely to bear children by males other than her husband.…”
Section: Do Maladaptive Traits Exist?mentioning
confidence: 99%